2013
DOI: 10.1177/0146167213499937
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Religion and God on Prosociality With the Ingroup and Outgroup

Abstract: Recent studies have found that activating religious cognition by priming techniques can enhance prosocial behavior, arguably because religious concepts carry prosocial associations. But many of these studies have primed multiple concepts simultaneously related to the sacred. We argue here that religion and God are distinct concepts that activate distinct associations. In particular, we examine the effect of God and religion on prosociality toward the ingroup and outgroup. In three studies, we found that religi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
137
3
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(163 citation statements)
references
References 53 publications
8
137
3
9
Order By: Relevance
“…In general, in-group cooperation among religious people might also lead to between-group competition, which in turn leads to out-group conflict and hostility ; see also Norenzayan, 2013). In parallel with this account, when people were primed with religious words, they showed greater in-group cooperation (Preston & Ritter, 2013) and increased level of negative attitudes toward value-violating out-groups (Johnson, Rowatt, & LaBouff, 2012). Thus, prejudice has a central role for religious groups in protecting their communities (see also Ramsay, Pang, Shen, & Rowatt 2014).…”
Section: Religion and Prejudicementioning
confidence: 88%
“…In general, in-group cooperation among religious people might also lead to between-group competition, which in turn leads to out-group conflict and hostility ; see also Norenzayan, 2013). In parallel with this account, when people were primed with religious words, they showed greater in-group cooperation (Preston & Ritter, 2013) and increased level of negative attitudes toward value-violating out-groups (Johnson, Rowatt, & LaBouff, 2012). Thus, prejudice has a central role for religious groups in protecting their communities (see also Ramsay, Pang, Shen, & Rowatt 2014).…”
Section: Religion and Prejudicementioning
confidence: 88%
“…If, on the whole, religious belief devalues the lives of nonbelievers, placing them outside the scope of moral concern, then people should believe that God prefers parochial choices that imply a decrease in the relative value of the lives of nonbelievers. However, if God is seen as promoting universal moral laws (20), and if those laws conflict with intergroup bias (21), participants should believe that God would prefer choices that more equally value human life regardless of religious identity.…”
mentioning
confidence: 99%
“…The inference was that collective rituals promoted norms favoring self-sacrifice to the group, of which the suicide attack is one extreme example. In an important study, Preston and Ritter (21) demonstrated that college students in the United States primed with God were more likely to help an outgroup member than an ingroup member, whereas participants primed with thoughts of a religious leader or religious institutions showed the opposite pattern of helping behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As such, religious social affiliations may impact an individual's moral behavior differently towards people within their group compared to outsiders (Hall, Matz, & Wood, 2010). Priming religious concepts and religion has been shown to increase prejudice (Preston & Ritter, 2013), violent behavior (Ginges, Hansen, & Norenzayan, 2009), and covert racial prejudice to outgroups, even when controlling for pre-existing religiousness (Johnson, Rowatt, & LaBouff, 2010). These effects of outgroup hostility or prejudices are not confined to Christian denominations, as similar findings have been found for Buddhists (Ramsay, Pang, Shen, & Rowatt, 2014), Muslims (Koopmans, 2014), and Hindus (Hunsberger, 1996).…”
Section: Introductionmentioning
confidence: 99%